Adversity Quotient sebagai Kunci Kesuksesan Penalaran Spasial dalam Pembelajaran Geometri - Pamungkas, Andini Siwi; Pramudya, Ikrar; Siswanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Spatial reasoning is a cognitive skill that plays an important role in geometry learning and is influenced by various factors, one of which is Adversity Quotient (AQ), a student's resilience in facing academic challenges. This study aims to analyze the spatial reasoning ability of junior high school students in solving geometry problems based on AQ categories. This study uses a qualitative approach with a case study design. This study included 64 seventh-grade students, categorized based on the Adversity Response Profile (ARP) Questionnaire adopted from Paul G. Stoltz to map students' AQ. Furthermore, five geometry test questions were used to measure spatial reasoning. Six students, two for AQ climbers, campers, and quitters, were interviewed to explore students' spatial reasoning. The results showed that climber students excelled in spatial visualization and mental rotation. Camper students tended to be less consistent, and quitter students had difficulty visualizing two-dimensional to three-dimensional relationships. These findings emphasize the importance of AQ in designing geometry learning strategies. The study's conclusion shows that Adversity Intelligence is an important factor in supporting the success of spatial reasoning for solving geometry problems. The implications of this research suggest that mathematics education, especially geometry, needs to focus not only on cognitive aspects but also on developing affective aspects such as resilience (adversity quotient).